Analisis Faktor Yang Mempengaruhi Produksi Perikanan Tangkap Di Indonesia Pada Periode 2020-2024 - Charlos Poltak Jeremia Lubis; Arivina Ratih (CV. ITTC INDONESIA, 2026)
Indonesia is the world's largest archipelagic country and has a large marine fisheries base that supports national food security. Even so, capture fisheries production across provinces still moves unevenly, which suggests that the use of production inputs has not been fully efficient. This study examines the effects of the number of fishermen, fishing vessels, and capture fisheries households on capture fisheries production in Indonesia during 2020-2024. The study applies a quantitative explanatory approach using secondary panel data from 33 provinces with complete observations for five years, resulting in 165 observations. The data were obtained from the Ministry of Marine Affairs and Fisheries (KKP). The analysis uses panel data regression, with model testing through the Chow and Hausman tests, and reports the Random Effect Model (REM) estimation used in the study. The results show that the number of fishermen has a positive and significant effect (β = 1.639; p < 0.05), the number of fishing vessels has the largest positive coefficient (β = 2.635; p < 0.05), and capture fisheries households have a negative and significant effect (β = -1.527; p < 0.05). Jointly, the three variables significantly explain production (F = 202.15; p < 0.05; R² = 0.790). The findings suggest that increasing production inputs needs to be balanced with resource-carrying capacity to prevent excess exploitation in capture fisheries.